Social accountability in frontline service delivery: Citizen engagement and provider response in four Indonesian districts. (20th October 2017) - Wetterberg, Anna; Hertz, Jana C.; Brinkerhoff, Derick W.
Abstract: Social accountability (SA) tools engage citizens in improving frontline service delivery. Contextual factors are increasingly recognized as key to the effectiveness and sustainability of SA. This article identifies micro‐level factors associated with attitudes and continued commitment to SA, drawing on 60 interviews with providers, clients and local officials at 15 primary health centres in four Indonesian districts. We found that healthcare providers and local governments demonstrated responsiveness to citizens not only in conducive contexts, but also in less favourable ones. State actors' perceptions of the appropriate role of citizens varied. We conclude that long‐term sustainability of citizen engagement in accountability relationships will depend upon alignment of providers' and citizens' expectations, along with supportive institutional incentives.